2008
DOI: 10.4161/cc.7.18.6699
|View full text |Cite
|
Sign up to set email alerts
|

Activation of DNA damage response signaling in mouse embryonic stem cells

Abstract: Mouse embryonic stem cells (mESC) are characterized by high proliferation activity. mESC are highly sensitive to genotoxic stresses and do not undergo G 1 /S checkpoint upon DNA-damage. mESC are supposed to develop sensitive mechanisms to maintain genomic integrity provided by either DNA damage repair or elimination of defected cells by apoptosis. The issue of how mESC recognize the damages and execute DNA repair remains to be studied. We analyzed the kinetics of DNA repair foci marked by antibodies to phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 23 publications
9
66
1
Order By: Relevance
“…However, mammalian ESC exhibit the robust induction of a DNA damage response that facilitates the elimination of damaged cells by apoptosis [4,37,44,50]. Consistent with previous reports [43], our results demonstrate that DNA damage response mechanisms in mESC include the recruitment of DNA repair components and the activation of gH2AX foci. Moreover, our results indicate that an additional mechanism for the maintenance of mESC genomic integrity relies on the increased activation of HR throughout the cell cycle, in marked contrast to fibroblasts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, mammalian ESC exhibit the robust induction of a DNA damage response that facilitates the elimination of damaged cells by apoptosis [4,37,44,50]. Consistent with previous reports [43], our results demonstrate that DNA damage response mechanisms in mESC include the recruitment of DNA repair components and the activation of gH2AX foci. Moreover, our results indicate that an additional mechanism for the maintenance of mESC genomic integrity relies on the increased activation of HR throughout the cell cycle, in marked contrast to fibroblasts.…”
Section: Discussionsupporting
confidence: 81%
“…1B). Previous studies in mESC and in mouse embryonic teratocarcinoma cells (mECC) also showed a high proportion of noninduced single and DSBs [43]. Both mESC and mECC are very rapidly dividing cells with similar cell cycle profiles and cell cycle duration, estimated at 10-12 h. It has been suggested that the high levels of DNA damage observed in mECC may be due to their rapid replication rate, perhaps as a consequence of incomplete maturation of replication forks [44].…”
Section: Hr Repair Proteins Bind To Sites Of Dna Damage Throughout Thmentioning
confidence: 99%
“…On the other hand, it has been shown that normal stem cells have only partially active DNA damage checkpoints. 24,32,33 This suggested that CSCs can actually be less prone to undergo irreversible growth arrest after exposure to DNA damaging agents. This, in turn, would result in an ineffective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mESCs display an elevated basal level of -H2AX, even in the absence of DSBs (Banath et al, 2009;Chuykin et al, 2008). Nevertheless, when H2AX phosphorylation is followed over time, mESCs and differentiated cells show a similar behavior with respect to foci formation and dissolution (Adams et al, 2010a;Chuykin et al, 2008). The reason for the high basal level of phosphorylated H2AX in mESCs is as yet unclear.…”
Section: Dna Damage Recognitionmentioning
confidence: 99%
“…In ESCs, ATM also becomes phosphorylated at serine 1981, relocates to DSBs and phosphorylates the histone www.intechopen.com variant protein H2AX within a few minutes post irradiation (Momcilovic et al, 2009). Notably, mESCs display an elevated basal level of -H2AX, even in the absence of DSBs (Banath et al, 2009;Chuykin et al, 2008). Nevertheless, when H2AX phosphorylation is followed over time, mESCs and differentiated cells show a similar behavior with respect to foci formation and dissolution (Adams et al, 2010a;Chuykin et al, 2008).…”
Section: Dna Damage Recognitionmentioning
confidence: 99%